Breastfeeding practices among slum mothers: a multivariate statistical analysis - I, Rafiqul; R, Mahfuzar; R, Mosfequr; IM, Nazrul (IIUM Medical Journal Malaysia, 2009)
Introduction: The aim of this study was to determine the differential patterns of mean duration of breastfeeding among mothers from slum areas in Rajshahi City, Bangladesh by using the multiple classification analysis (MCA). Materials and Methods: The data for this study was collected from mothers from slum areas of 8 different slums of Rajshahi City Corporation who had had at least one child at the time of interview. Results: We showed that the overall mean duration of breastfeeding was 24.66 months for all women, which may show considerable impact on fertility around slum areas in near future. Conclusion: Of all the selected variables in MCA, it was seen that the current age of the children and the body mass index of the respondents appear as the strongest important determinants of duration of breastfeeding and other variables play relatively less important role on the duration of breastfeeding.